"Shockvertising": conceptual interaction patterns as constraints on advertising creativity - Pérez-Sobrino, Paula (Círculo de Lingüística Aplicada a la Comunicación, 2016)
This paper explores the conceptual scaffolding of six shockvertisements raising awareness on environmental preservation. The analysis shows that advertisers make use of a finite set of cognitive operations (metaphor in interaction with metonymy) to downgrade people through the attribution of animal or plant characteristics and to enhance animals and plants through the opposite process. The simple and universal nature of these mappings, in which ’defenselessness’ emerges as the quintessential attribute common to people, animals, and plants, assures advertisers that their message will be interpreted straightforwardly and almost effortlessly by viewers of different countries and cultural backgrounds (yet with some variation in the degree of communicative impact).